Strategies for Implementation of the New Antimalarial Drug Policy in Uganda: Workshop Report, Entebbe, October 4–5, 2006 - Mubangizi, Deusdedit; Kidde, Saul; Tetteh, Gladys (Management Sciences for Health, 2007)
The National Drug Authority (NDA) of Uganda, with funding from the U.S. Agency for International Development’s Uganda Mission through the Rational Pharmaceutical Management Plus Program of Management Sciences for Health, held a national consultative workshop to discuss NDA’s action plan for implementation of the new antimalarial medicine policy, which includes artemisinin-based combination therapy as first-line treatment for uncomplicated malaria. A team of 28 stakeholders was drawn from national and support agencies in Uganda for a two day workshop (October 4–5, 2006). The workshop targeted stakeholders providing support for the new antimalarial treatment policy by executing malaria control and pharmaceutical management activities. Participants included researchers, policy makers, clinicians, pharmacists, procurement specialists, and district health workers, as well as members or staff from health professional associations, development partners, and agencies responsible for implementing public health policy.